Conflict management in digital business : new strategy and approach - Özsungur, Fahri, 1981- (Emerald Publishing Limited, 2022)
Today's business world is under constant digital threats that can cause unpredictable damage and weaken the competitiveness of businesses. With digital transformation risks and cyber-attacks increased by extraordinary situations such as the recent pandemic, new approaches are needed in the management of these emerging digital conflicts to develop sustainable business strategies and become a robust business of the future. Conflict Management in Digital Business: New Strategy and Approach is a pioneering and innovative guide in the context of digital conflicts in the value chain of businesses and on digital conflicts in business management and strategy. Conflict management is discussed in the context of issues of production and planning, logistics, marketing, procurement, technology development, human resource management, and business infrastructure. Sectoral issues with conflicting businesses, organizational behavior, digital sustainability, cyber business management, cyber-attack, and cyberwarfare strategies for businesses are discussed in detail to bring crucial principles in the context of management and strategy to all businesses that desire to be a business of the future. Providing readers with a unique guide of how businesses can achieve resilience to digital conflict, Conflict Management in Digital Business helps prepare for unexpected situations such as pandemics, to maintain competitive advantage, and illuminating pathways to turn conflicts caused by extraordinary situations into opportunities.